Maximum city Bombay lost and found - Mehta, Suketu (New Delhi, India Penguin Books India Pvt. Ltd, 2006)
A native of Bombay, Suketu Mehta gives us an insider's view of this stunning metropolis. He approaches the city from unexpected angles, taking us into the criminal underworld of rival Muslim and Hindu gangs; following the life of a bar dancer raised amid poverty and abuse; opening the door into the inner sanctums of Bollywood; and delving into the stories of the countless villagers who come in search of a better life and end up living on the sidewalks.
Personal geography -- The country of the No -- Two currencies -- Powertoni -- The 1992-93 riots -- Elections 1998 -- The Saheb -- Mumbai -- Number two after Scotland Yard -- Ajay Lal: the blasts and the gangwar -- Encounter -- Black collar workers -- Mohsin: The D company -- Satish: The Dal Badlu -- Chotta Shakeel: The Don in exile -- Vadapav eater's city -- A city in heat -- Monalisa dances -- Golpitha -- Two lives: Honey / Manoj -- New Year's Eve -- Distilleries of pleasure -- Vidhu Vinod Chopra: Mission Kashmir -- Mahesh Bhatt's wound -- The struggler and the goddess -- Accused: Sanjay Dutt -- Dreamworld / underworld -- Memory mines -- Mayur Mahal multipurpose -- A world of children -- Sone ki Chidiya -- Girish: a tourist in his city -- Babbanji: runaway poet -- Adjust -- Good-bye world -- A self in the crowd.
Keywords: Mehta, Suketu -- Travel -- India -- Mumbai; Mumbai (India) -- Description and travel